Pharmacogenetic aspects of substance use disorders - A. O. Kibitov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
The substance use disorders Diseases of substance dependence (SAW) represent the «pharmacogenetic» diseases caused by abnormal and genetically determined response of the CNS to use of the substance of abuse (SA), conscious and regulated by person itself. Genetic differences in the pharmacodynamics of SA can shape the individual level of genetic risk for disease, which can be calculated, provided valid identification of genetic markers that distinguish the «responders» (ill) from «non-responders» (healthy). Further genetic studies in addiction using strict evidence-based design and pathogenetic panel with dopamine and opioid genes will help to assess: 1) the genetic influence on the effects of SA, depending on the level of genetic risk; 2) to assess the level of genetic risk itself; 3) the effect of genetic variants on the effectiveness of pharmacotherapy of the disease. It is necessary to consider the impact of ethnicity, gender and age of patients, concomitant somatic and mental illness, combined administration of other medicines and variety of substances of abuse, tolerance, poor compliance in the absence of objective laboratory tests.